Anti-Mastigina activities of eight contact lens solutions. - Niszl, I A (1995)
The effects of eight contact lens solutions on a Mastigina sp., which was associated with the infected eye of a patient, were studied. The solutions which killed the organism promptly were those which are used for gas-permeable and hard contact lenses. Some solutions for soft contact lenses were more effective than others.